2011
DOI: 10.1002/hep.24400
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible transcription factor 2α promotes steatohepatitis through augmenting lipid accumulation, inflammation, and fibrosis

Abstract: Oxygen dynamics in the liver is a central signaling mediator controlling hepatic homeostasis, and dysregulation of cellular oxygen is associated with liver injury. Moreover, the transcription factor relaying changes in cellular oxygen levels, hypoxia-inducible factor (HIF), is critical in liver metabolism and sustained increase in HIF signaling can lead to spontaneous steatosis, inflammation, and liver tumorigenesis. However, the direct responses and genetic networks regulated by HIFs in the liver are unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(177 citation statements)
references
References 38 publications
7
166
1
Order By: Relevance
“…A very elegant and recent study has provided further evidence for relationships between HIFs and hepatic fibrogenesis by employing hepatocyte-specific von Hippel Lindau protein (VHL) and HIF-1 or HIF-2 mouse mutants [88]. When mice with liver conditional disruption of VHL (and then with an increased expression of both HIF-1 and HIF-2) were treated for 2 weeks with an ethanol-containing diet, they developed increased fibrosis.…”
Section: Hypoxia and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…A very elegant and recent study has provided further evidence for relationships between HIFs and hepatic fibrogenesis by employing hepatocyte-specific von Hippel Lindau protein (VHL) and HIF-1 or HIF-2 mouse mutants [88]. When mice with liver conditional disruption of VHL (and then with an increased expression of both HIF-1 and HIF-2) were treated for 2 weeks with an ethanol-containing diet, they developed increased fibrosis.…”
Section: Hypoxia and Angiogenesismentioning
confidence: 99%
“…When mice with liver conditional disruption of VHL (and then with an increased expression of both HIF-1 and HIF-2) were treated for 2 weeks with an ethanol-containing diet, they developed increased fibrosis. Interestingly, this increase was prevented when simultaneous deletion of HIF-2 (but not HIF-1), was carried out, suggesting that HIF-2 may prevail in regulating hepatic fibrogenesis [88].…”
Section: Hypoxia and Angiogenesismentioning
confidence: 99%
“…The Vhl F/F;AlbERT2cre mice were described previously and treated with tamoxifen for 5 days and then returned to a chow diet for 11 days prior to euthanasia (22). Hepatic deletion of VHL results in constitutive activation of HIF2␣ in the liver, leading to rapid inflammation, lipid accumulation, and fibrosis (22). For BrdU incorporation experiments, miniosmotic pumps containing sterile BrdU were implanted subcutaneously, and mice were euthanized 6 days later.…”
Section: Animals and Treatments-the Hnf4amentioning
confidence: 99%
“…A recent study found elevated BMP7 levels in a hepatitis B mouse model of HCC and further identified elevated BMP7 in human cirrhotic liver and HCC samples (36). To assess whether the induction of Bmp7 in Hnf4a F/F;AlbERT2cre ϩ tamoxifen mice was associated with steatosis and liver damage or cellular proliferation, Bmp7 levels were measured in the Vhl F/F;AlbERT2cre mouse, which displays hepatic steatosis, inflammation, and fibrosis but not cellular proliferation (22). Transglutaminase 2 (Tgm2), a marker of fibrosis, is significantly up-regulated in Vhl F/F;AlbERT2cre ϩ tamoxifen mice, but Bmp7 levels remain nearly undetectable (Fig.…”
Section: Loss Of Hnf4␣ Induces Hepatotrophic Factor Bone Morphogenetimentioning
confidence: 99%
“…HIF-induced transcription promotes angiogenesis, erythropoiesis, metastasis and metabolic reprogramming, such as shifting cell metabolism from oxidative phosphorylation to glycolysis. HIF activation due to hypoxia or loss of VHL function also reprograms lipid metabolism leading to lipid accumulation (Huss et al, 2001;Boström et al, 2006;Rankin et al, 2009;Kucejova et al, 2011;Qu et al, 2011;Walter et al, 2014).…”
Section: Mitochondria As Redox Signaling Nodesmentioning
confidence: 99%